4-Amino-2-Trifluoromethyl-Phenyl Retinate Inhibits Proliferation, Invasion, and Migration of Breast Cancer Cells by Independently Regulating CRABP2 and FABP5 [Retraction] - Ju J; Wang N; Wang J; Wu F; Ge J; Chen F (Drug Design, Development and Therapy, 2024)
Ju J, Wang N, Wang J, Wu F, Ge J, Chen F. Drug Des Devel Ther. 2018;12:997-1008. At the request of the authors, the Editor and Publisher of the journal Drug Design, Development and Therapy have retracted the published article. Following publication of the article, the authors raised concerns about the duplication of images from Figure 2 with those from an unrelated article and the duplication of images within Figure 8. Specifically,